Scintillation arcs in low-frequency observations of the timing-array millisecond pulsar PSR J0437–4715 - Bhat, N.; Ord, S.; Tremblay, Steven; McSweeney, S.; Tingay, Steven (Institute of Physics Publishing, 2016)
© 2016. The American Astronomical Society. All rights reserved. Low-frequency observations of pulsars provide a powerful means for probing the microstructure in the turbulent interstellar medium (ISM). Here we report on high-resolution dynamic spectral analysis of our observations of the timing-array millisecond pulsar PSR J0437-4715 with the Murchison Widefield Array (MWA), enabled by our recently commissioned tied-array beam processing pipeline for voltage data recorded from the high time resolution mode of the MWA. A secondary spectral analysis reveals faint parabolic arcs akin to those seen in high-frequency observations of pulsars with the Green Bank and Arecibo telescopes. Data from Parkes observations at a higher frequency of 732 MHz reveal a similar parabolic feature with a curvature that scales approximately as the square of the observing wavelength (?2) to the MWA's frequency of 192 MHz. Our analysis suggests that scattering toward PSR J0437-4715 predominantly arises from a compact region about 115 pc from the Earth, which matches well with the expected location of the edge of the Local Bubble that envelopes the local Solar neighborhood. As well as demonstrating new and improved pulsar science capabilities of the MWA, our analysis underscores the potential of low-frequency pulsar observations for gaining valuable insights into the local ISM and for characterizing the ISM toward timing-array pulsars.